The relationship between sleep disturbance in late pregnancy and labor outcomes - aalrazek, Aida; Ayoub, Gamila; Batiha, Abdul-Monim; Al-Zaru, Ibtisam; Alhalaiqa, Fadwa; Farahat, Hoda; AlBashtawy, Mohammed (International Journal of Health, 2016)
Background: Inadequate sleep is a common problem among women, in part as a result of a deficiency of information about its influence on health; particularly, the effect of sleep deprivation during pregnancy on labor outcomes (maternal and fetal).Objective: To study the correlations between sleep duration and labor outcomes among women in late pregnancy.Method/ Material: A prospective descriptive study was conducted at four settings in the Menoufiya Governorate of Egypt. A convenience sample technique was used. The study sample involves 200 pregnant women. Data collection extended from April 2013 to January 2014.Result: The results revealed that: a) most of the women in the studied sample (50%) suffered from sleep disturbance in late pregnancy at gestational age above 37 weeks and b) that only 24% suffered sleep disturbance between 28-32 weeks. It takes 30-60 min for majority of the women in the research sample (42.5%) to fall asleep at night; only (10%) take <5 min to fall asleep at night. No significant difference between the total hours of sleep and birth duration was found in this study.Conclusion: The study concluded that healthcare providers should advise women during pregnancy to get adequate sleep duration of at least eight hours and provide prenatal assessments include the sleep quantity and quality because they both affect the duration of labor and type of delivery.Â